4H-SiC SACM Avalanche Photodiode With Low Breakdown Voltage and High UV Detection Efficiency - Xiaolong Cai; Dong Zhou; Sen Yang; Hai Lu; Dunjun Chen; Fangfang Ren; Rong Zhang; Youdou Zheng (IEEE Photonics Journal)
In this paper, a high-performance 4H-SiC separated absorption charge multiplication ultraviolet avalanche photodiode (APD) with low breakdown voltage is designed and fabricated. The room temperature dark current of the APD remains at ∼0.1 pA level ( $\rm{\sim}29\;\text{pA/ cm}^{- 2}$ ) when reverse bias is below 50 V and then rises by several orders of magnitude before avalanche breakdown occurs. An avalanche gain up to 106 is achieved at 67 V. Based on secondary ion mass spectroscopy measurement, the electric field distribution within the as-fabricated APD is numerically simulated. The ionization ratio of Al in the p-type charge control layer is estimated to be 40%. The frequency dispersion phenomenon in capacitance–voltage (C-V) measurement should be caused by structural defects existing within the APDs, which may also be the source of the enhanced dark current before avalanche breakdown. The room-temperature maximum quantum efficiency is ∼80% at 270 nm with an ultraviolet (UV)/visible rejection ratio more than 10 4.